SERUM TRACE ELEMENTS IN DIAGNOSIS OF BREAST MALIGNANCY - Arooj, Burarah; Ahmed, Sameen; Saleem, Mahjabeen; Khurshid, Rukhshan; Zia, Muddasar (Journal of Ayub Medical College Abbottabad, 2012)
Background: Breast cancer is a highly heterogeneous disease globally. The absolute risk of breast cancer increases with age and is higher in postmenopausal women. This study tried to find out role of serum trace elements (cadmium, cobalt, copper and zinc) and biomarkers in diagnosis of breast malignancy. Methods: Levels of serum trace elements were estimated by atomic absorption spectrophotometry in serum samples of 23 breast cancer patients of stage III. Analysis of protein pattern was observed by sodium dodecyl polyacrylamide gel electrophoresis (SDS-PAGE). Results: In menstruating women, the mean serum level of cadmium, copper and cobalt were significantly lowered as compared to control, however, zinc showed no significant difference. In premenopausal and postmenopausal women, the mean serum level of cadmium, copper, cobalt and zinc was decreased significantly in patients as compared to controls (p<0.001). The ratio of Cu/Zn was also decreased in patients when compared to controls. Three major peptide bands with molecular weights of 33 kDa, 52 kDa and 185 kDa appeared in these samples when subjected to SDS PAGE. Conclusions: Serum trace elements are significantly lower in breast cancer patients compared to controls. The exact mechanism responsible for the alterations in trace element levels in patients with breast cancer is unclear and requires further evaluation. Gel electrophoresis may be important to find out breast cancer markers that may help in diagnosing the disease and response to treatment. Keywords: Metals, Breast Cancer, Protein Markers